TEACHING FOREIGN LANGUAGES TO INTERNET GENERATION: NEW CHALLENGES - Kuznetsova, Tatiana; Kuznetsov, Igor; Artyushina, Ph. D. Galina G. (Revista Inclusiones, 2021)
The use of Information Technologies presents new challenges to foreign language teaching. To respond to these challenges teachers should consider the impact of IT on consciousness and style of thinking of their users, primarily of the so-called Generation Y, or Internet generation. The paper examines some of the changes brought about by computer technologies, in particular, what is usually described as “clip thinking” and “digital amnesia”. Taking as an example the use of printed and computerized dictionaries, the authors come to the conclusion that the main task of the teacher is to help students find the right strategy and make informed choices about which dictionary to use in a particular situation.